The influence of Brand trust, Social Media Marketing and e-WOM on interest purchasing in Snake Socks products in Surabaya - Moch Rifan al faizin (Journal of World Conference (JWC), 2019)
The purpose of this research are for known as brand trust, social media marketing, electronic word of mouth and purchase intention of Snake socks consuments product in Surabaya. .This research is a quantitave. The population and samples are based upon questionnaire that had been given to 100 respondents of Snake Socks consuments product in Surabaya. Data retrieval techniques by interview, observation and questionnaire. The method used is quantitative research method. For the method of data analysis using Path Analyze) with IBM SPSS 23.0 Data analysis that had been use are validity test, reability test, classic assumption test, and multiple linear analysis test. The result of his study showed that partially brand trust (X1), social media marekting (X2),electronic word of mouth (X3) has positive significant positive significant toward purchase intention (Y). While brand image gives impact toward two variables electronic word of mouth and purchase intention as the intervening variable.The research has a significant correlation towards employe performance (Y) the value is < 0,05.